Codelivery of doxorubicin and MDR1-siRNA by mesoporous silica nanoparticles-polymerpolyethylenimine to improve oral squamous carcinoma treatment - Wang D (Dove Medical Press, 2017)
Dandan Wang,1,* Xiaowei Xu,2,* Kai Zhang,3 Bin Sun,4 Lu Wang,1 Lin Meng,1 Qilin Liu,4 Changyu Zheng,5 Bai Yang,3 Hongchen Sun1,3,6 1Department of Pathology, School and Hospital of Stomatology, Jilin University, Changchun, People’s Republic of China; 2Department of Periodontology, School and Hospital of Stomatology, Jilin University, Changchun, People’s Republic of China; 3State Key Laboratory of Supramolecular Structure and Materials, College of Chemistry, Jilin University, Changchun, People’s Republic of China; 4Department of Oral and Maxilloficial Syrgery, School and Hospital of Stomatology, Jilin University, Changchun, People’s Republic of China; 5Molecular Physiology and Therapeutics Branch, National Institute of Dental and Craniofacial Research, National Institutes of Health, Bethesda, MD, USA; 6Key Laboratory of Science and Technology for Stomatology Nanoengineering, The Education Department of Jilin Province, Changchun, People’s Republic of China *These authors contributed equally to this work Abstract: Oral cancer is a type of head and neck cancer that is the seventh most frequent cancer and the ninth most frequent cause of death globally. About 90% of oral cancer is of squamous cell carcinoma type. Surgery and radiation with and without chemotherapy are the major treatments for oral cancer. Better advanced treatment is still needed. Multidrug resistance plays an important role in failure of oral cancer chemotherapy. In this study, we tried to fabricate a novel nanoparticle that could carry both MDR1-siRNA to block MDR1 expression and doxorubicin (DOX), a chemotherapy drug, into cancer cells in order to directly kill the cells with little or no effect of multidrug resistance. Results showed that mesoporous silica nanoparticles (MSNP) can be modified by cationic polymerpolyethylenimine (PEI) to obtain positive charges on the surface, which could enable the MSNP to carry MDR1-siRNA and DOX. The transfection efficiency assays demonstrated that the MSNP-PEI-DOX/MDR1-siRNA was efficiently transfected into KBV cells in vitro. KBV cells transfected with MSNP-PEI-DOX/MDR1-siRNA could effectively decrease gene expression of MDR1 (~70% increase after 72 hours posttreatment) and induce the apoptosis of KBV cells (24.27% after 48 hours posttreatment) in vitro. Importantly, MSNP-PEI-DOX/MDR1-siRNA dramatically reduced the tumor size (81.64% decrease after 28 days posttreatment) and slowed down tumor growth rate compared to the control group in vivo (P<0.05). In the aggregate, newly synthesized MSNP-PEI-DOX/MDR1-siRNA improves cancer chemotherapy effect in terms of treating multidrug-resistant cancer compared to DOX only, clearly demonstrating that MSNP-PEI-DOX/MDR1-siRNA has potential therapeutic application for multidrug-resistant cancer in the future. Keywords: oral squamous carcinoma, doxorubicin, MDR1, mesoporous silica nanoparticles, polymerpolyethylenimine